Knowledge, Perception, Motivation and Expectations of Nursing and Midwifery Students on Exit Exam in Bengkulu City, Indonesia - Ida Samidah; Murwati; Tita Septi Handayani (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Public knowledge regarding health services has been increasing significantly in the recentyears and it has an effect on increasing community demands for quality health services. Therefore, healthworkers with good skills, intelligent, and communicative are needed. Good competence is also needed incarrying out their roles and functions according to the code of ethics The competencies of health workergraduates are different in every regions in Indonesia. The majority of health workers perceive that theircurrent competencies are not in accordance with their expectations. To ensure that health workers producedby educational institutions have the same competence, all health worker graduates are required to take acompetency test as a requirement for obtaining a registration certificate. Exit exam is a competency test thatis conducted as a requirement for graduation. This study aims to provide an overview of the relationshipbetween the knowledge, perceptions, motivation and expectations of nursing and midwifery students onthe competency test as a graduation requirement. Methods: This is a mix-method study (A quantitativeand qualitative methods were used). The quantitative method used was non-experimental, with a crosssectionalapproach, and qualitative methods to find out information about the perceptions, motivations andexpectations of respondents about the implementation of the competency exam as a passing requirement.The number of samples in this study were 246 respondents, consisting of DIII midwifery, Nursing DIII andnurses (82 respondents for each colleges). Results: The results of the study based on the path analysis showedthat education had no influence on knowledge, respondents’ perceptions and expectations of the competencytest, but had an influence on motivation (P = < 0.01). Knowledge does not affect on perception, motivationor expectation, while for perception variable affects on motivation (P = 0.026) and expectation (P= <0.01).Conclusion: Respondents’ expectations will be directly influenced by motivation and perception.